2021
DOI: 10.5418/ra2021.v17i33.11946
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica erosiva e progradacional das praias de Atafona e Grussaí (RJ), 1954-2019

Abstract: Os litorais são regiões dinâmicas onde agentes atmosféricos, continentais e marinhos interagem e nem sempre atuam em equilíbrio. Como resultado, processos de recuo, avanço e de estabilidade atuam na costa modificando sua morfologia ao longo do tempo. Neste contexto, o trabalho busca realizar o mapeamento e análise multitemporal dos processos de erosão e progradação observados nas praias de Atafona e Grussaí (São João da Barra – RJ, Brasil). A metodologia baseou-se na reunião de séries temporais de imagens dos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…Rocha et al (2018) investigating 10 years of shoreline behavior, using beach profiles, showed that the erosive trend prevails only in Atafona Beach, and in Grussaí, the shoreline trend to sedimentation. With more detailed cartographical approach, Vasconcelos et al (2021), using historical aerophotogrammetry between 1954 and 2019, showed that between Atafona and Grussaí, the shoreline presents different behaviors, with erosion in Atafona and sedimentation in Grussaí, with no losses in area. Souza et al (2022) do not mention that the shoreline presents a continuous prograding trend in the northern sector of PSRD, in Gargau Beach, since 1926.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rocha et al (2018) investigating 10 years of shoreline behavior, using beach profiles, showed that the erosive trend prevails only in Atafona Beach, and in Grussaí, the shoreline trend to sedimentation. With more detailed cartographical approach, Vasconcelos et al (2021), using historical aerophotogrammetry between 1954 and 2019, showed that between Atafona and Grussaí, the shoreline presents different behaviors, with erosion in Atafona and sedimentation in Grussaí, with no losses in area. Souza et al (2022) do not mention that the shoreline presents a continuous prograding trend in the northern sector of PSRD, in Gargau Beach, since 1926.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusions about paleogeography presented by Souza et al (2022) substantially disagree with the previously published literature in the last 30 years, particularly since the works of Dominguez et al (1983), Martin et al (1985), Suguio et al (1985), Dominguez et al (1992); Martin et al (1993), Dias and Kjerfve (2009), Dominguez (2009), Rocha et al (2019), Figueiredo et al (2021), Fernandez et al (2022 and Rocha et al (2022), andDominguez (2023), which mainly based on OSL and radiocarbon dating, indicate that construction of the deltaic plain began in the Mid to Late Holocene, correlated with sea-level behavior. From the perspective of short-term evolution, there are a large number of papers that use satellite images, historical aerial photographs, and detailed topographical surveys to indicate that the deltaic plain has been increasing in area during the last decades (Vasconcelos et al, 2016(Vasconcelos et al, , 2021Rocha et al, 2018;Besset et al, 2019;Costa et al, 2020), although locally, only in Atafona Beach, the shoreline retreat (Vasconcelos et al, 2016(Vasconcelos et al, , 2021Rocha et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Esses terrenos inundáveis estão pontilhados por diversas lagunas e banhados e apresentam uma complexa associação de solos com altos teores de sais e enxofre em sua matriz, abrangendo Organossolos, Planossolos Nátricos, Gleissolos Tiomórficos e Gleissolos Sálicos.No entorno da desembocadura do Rio Paraíba do Sul desenvolve-se um sistema de feixes truncados de cordões arenosos em linha de costa progradante, demonstrando uma notável variação morfodinâmica com períodos de progradação, alternados com períodos de retrogradação do delta do Rio Paraíba do Sul nos últimos 5.000 anos. O processo de erosão costeira experimentado pela vila de Atafona, agravado pela intervenção humana na bacia do Rio Paraíba do Sul, ressalta a fragilidade morfodinâmica dessa área(VASCONCELOS et al, 2021).Figura 20. Mosaico de ambientes deposicionais fluviodeltaicos, marinhos e lagunares do vasto brejo do delta do Rio Paraíba do Sul.…”
unclassified
“…Esses terrenos inundáveis estão pontilhados por diversas lagunas e banhados e apresentam uma complexa associação de solos com altos teores de sais e enxofre em sua matriz, abrangendo Organossolos, Planossolos Nátricos, Gleissolos Tiomórficos e Gleissolos Sálicos.No entorno da desembocadura do Rio Paraíba do Sul desenvolve-se um sistema de feixes truncados de cordões arenosos em linha de costa progradante, demonstrando uma notável variação morfodinâmica com períodos de progradação, alternados com períodos de retrogradação do delta do Rio Paraíba do Sul nos últimos 5.000 anos. O processo de erosão costeira experimentado pela vila de Atafona, agravado pela intervenção humana na bacia do Rio Paraíba do Sul, ressalta a fragilidade morfodinâmica dessa área(VASCONCELOS et al, 2021).Figura 20. Mosaico de ambientes deposicionais fluviodeltaicos, marinhos e lagunares do vasto brejo do delta do Rio Paraíba do Sul.…”
unclassified